Exploring the impact of an Aboriginal Health Worker on hospitalised Aboriginal experiences: lessons from cardiology. - Taylor, Katherine; Thompson, Sandra; Smith, J.; Dimer, L.; Ali, Mohammed; Wood, M. (Australasian Medical Publishing Company Pty Ltd, 2009)
To enhance Aboriginal inpatient care and improve outpatient cardiac rehabilitation utilisation, a tertiary hospital in Western Australia recruited an Aboriginal Health Worker (AHW). Interviews were undertaken with the cardiology AHW, other hospital staff including another AHW, and recent Aboriginal cardiac patients to assess the impact of this position. The impact of the AHW included facilitating culturally appropriate care, bridging communication divides, reducing discharges against medical advice, providing cultural education, increasing inpatient contact time, improving follow-up practices and enhancing patient referral linkages. Challenges included poor job role definition, clinical restrictions and limitations in AHW training for hospital settings. This study demonstrates that AHWs can have significant impacts on Aboriginal cardiac inpatient experiences and outpatient care. Although this study was undertaken in cardiology, the lessons are transferable across the hospital setting.